-39*(23-13)=-39*23-(-39)*13

Simple and best practice solution for -39*(23-13)=-39*23-(-39)*13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -39*(23-13)=-39*23-(-39)*13 equation:


Simplifying
-39(23 + -13) = -39 * 23 + -1(-39) * 13

Combine like terms: 23 + -13 = 10
-39(10) = -39 * 23 + -1(-39) * 13

Multiply -39 * 10
-390 = -39 * 23 + -1(-39) * 13

Multiply -39 * 23
-390 = -897 + -1(-39) * 13

Multiply -1 * -39
-390 = -897 + 39 * 13

Multiply 39 * 13
-390 = -897 + 507

Combine like terms: -897 + 507 = -390
-390 = -390

Add '390' to each side of the equation.
-390 + 390 = -390 + 390

Combine like terms: -390 + 390 = 0
0 = -390 + 390

Combine like terms: -390 + 390 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (-3)*4=4*(-3) | | 52z+12= | | 106-5x=22x+19 | | z*2+8*z+17=0 | | 2x+13=-15 | | 4(x+2)=15 | | 5X+X^2=100 | | 9y-16=20 | | 7x(-1)=35 | | 6(x+4)+8=11x-5(x-4) | | 2x=79 | | u^2+2u-3= | | .06x=1750 | | 36*3= | | 4(3z-1)-5(z+8)=3(z+1) | | 1.9=.03x-58.31 | | 1737=-36x+73989 | | 31x=93 | | 6x=-27 | | -8(t-4)-(t+3)=10 | | 4x+y=-12 | | 9.24x-3.52=3.83x+41.924 | | x+4y=-3 | | 25=.5x | | 500=200x | | xl=200 | | 1750=.05x | | x+96+48=180 | | -12=x+14 | | x-7.3=-6.9 | | a-5=-11 | | x+3=50 |

Equations solver categories